Earnings Management in Response to Corporate Income Tax Rates Changes - Hania Galuh Pratiwi; Fajar Nurdin (Jurnal Akuntansi dan Perpajakan, 2023)
This study also aims to test the level of company earnings management before and after the new Corporate Income Tax rate in Law Number 02 of 2020 is set at 22%. The research was conducted on health sector companies listed on the Indonesia Stock Exchange (IDX) in 2018-2021. There were 25 populations and from these populations, 13 sample companies were selected using the purposive sampling method. The data analysis technique used is the paired t-test difference test. Based on data analysis, there were significant differences in discretionary accrual levels before and after the new Corporate Income Tax rate was determined. This means that the company conducts earnings management in response to Corporate Income Tax rates changes.